Teacher Unions in Political Transitions: The South African Democratic Teachers' Union (SADTU) and the Dying Days of Apartheid, 1990–1993. (April 2014) - Amoako, Samuel
The negotiation to end apartheid – which was initiated in secret in the 1980s – solidified in the 1990s when FW de Klerk unbanned the African National Congress (ANC), South African Communist Party (SACP), Pan African Congress (PAC) and other political and social movements, as well as struggle icons, prominent among whom was Mandela. The South African Democratic Teachers' Union (SADTU) emerged within the euphoria surrounding Mandela's release and the negotiations to end apartheid. SADTU combined its educational struggles with the political struggle to end apartheid rule. Drawing on documentary (mainly archival), newspaper reports and oral evidence, this article examines SADTU's struggles for recognition, its resistance against education restructuring, and its defiance campaign against inspection from 1990–1993. I suggest that SADTU's contentions during the period were rooted in the political struggle to end apartheid rule since it regarded the apartheid education departments as illegitimate structures needing to be dismantled. In addition, the socio-economic undercurrents that characterized the transition were carried into education restructuring and thus pushed SADTU into militancy.